2001
DOI: 10.1042/bst0290408
|View full text |Cite
|
Sign up to set email alerts
|

Can we identify the forces that drive the folding of integral membrane proteins?

Abstract: Protein folding has been at the forefront of molecular cell biology research for several years. However, integral membrane proteins have eluded detailed molecular level study until recently. One reason is the often apparently insurmountable problem of mimicking the natural membrane bilayer with lipid or detergent mixtures. There is nevertheless a large body of information on lipid properties and in particular on phosphatidylcholine and phosphatidylethanolamine lipids, which are common to many biological membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 1 publication
1
9
0
Order By: Relevance
“…Significantly, the latter process was directly regulated by varying the membrane lipid compositon. A similar result was obtained for the integral membrane proteins bacteriorhodopsin and the OmpA protein of Escherichia coli (Booth et al, 2001). These two in vitro studies demonstrated that "overall [protein] folding efficiency seem[s] to be controlled by particular properties of the lipid bilayer‰.…”
supporting
confidence: 68%
“…Significantly, the latter process was directly regulated by varying the membrane lipid compositon. A similar result was obtained for the integral membrane proteins bacteriorhodopsin and the OmpA protein of Escherichia coli (Booth et al, 2001). These two in vitro studies demonstrated that "overall [protein] folding efficiency seem[s] to be controlled by particular properties of the lipid bilayer‰.…”
supporting
confidence: 68%
“…The experimental determination of folding pathways in membrane proteins has lagged behind that of soluble proteins because the presence of lipids or detergents complicate both the experimental setup and the interpretation of folding studies of membrane proteins (44,45). Additionally, the higher stability of TM helices compared with soluble helices often prevents their denaturation (46). Only two proteins have been refolded from a completely unfolded state: bacteriorhodopsin (47), which also contains seven-TM helices, and OmpA (48), a ␤-barrel protein.…”
Section: Discussionmentioning
confidence: 99%
“…There are four kinds of retinal (rhodopsin-like) proteins in the membrane of archaeal bacteria: bacteriorhodopsin (BR), halorhodopsin (HR), sensory rhodopsin I (sRI) and phoborhodopsin (pR, also called sensory rhodopsin II, sRII) (1). The former two act as light-driven ion pumps (2)(3)(4)(5)(6)(7)(8)(9)(10)(11) while the latter two are photosensory receptors (12)(13)(14)(15)(16)(17). These four retinal proteins have the same tertiary structure, in which they have seven transmembrane-helices and a retinal chromophore bound to a conserved lysine residue on the seventh helix (G-helix) via a protonated Schiff base.…”
Section: Introductionmentioning
confidence: 99%